Formulation and evaluation of extended-release solid dispersions of Chlorpheniramine maleate by solvent evaporation method - علي, محمد; وهاد ابراهيم , (Latakia University Journal -Medical Sciences Series, 2023)
Chlorpheniramine maleate (CPM) is generally considered to be as a first generation short-acting antihistamine which commonly used as an anti-allergic drug. However, it is characterized by a wide range of side effects at therapeutic doses such as sedation and drowsiness which has led to the development of pharmaceutical formulations that prevent or alleviate these undesirable effects. CPM is classified as a highly water-soluble compound but is also able to cross the CNS and cause sedation and drowsiness. It is typically administered 4-6 times a day, which negatively impacts patient compliance and treatment’s efficacy. This research aims to use solid dispersion technique (SD), relying on solvent evaporation in the preparation of an extended-release form of CPM using Ethyl Cellulose (EC) as a water-insoluble polymer and controlled release agent. The effect of ratio (Drug: Polymer) on drying yield, entrapment efficiency and percentage of drug released over time was investigated. Ultimately, the prepared formulations did not show any significant difference in terms of yield or entrapment efficiency with varying (drug: polymer) ratios. Furthermore, in-vitro dissolution tests showed a decrease in the amount of drug released with an increase in the amount of ethyl cellulose. A controlled release of CPM was achieved, which is compatible with the specific conditions of the US pharmacopeia, at a (1:7) drug to polymer ratio.